PENINGKATAN KAPASITAS KETERAMPILAN LITERASI DI KOMUNITAS ANAK LUKU MELALUI PENERAPAN SISTEM AMONG - Westri Andini, Dinar; Praheto, Biya Ebi; Indah Purnama Sari, Dyan (Universitas PGRI Yogyakarta, 2024)
Literacy is often defined as the ability to read and write, so the actual concept needs to be applied. There are several efforts to develop literacy skills. The aim of this service is to increase the capacity for literacy skills in the LUKU children's community through implementing the among system using 3 principles, namely momong, among and ngemong. The method for implementing this service activity is through direct partner involvement and is implemented through 3 principles in the among system. Service activities were carried out at the LUKU Children's Community with 25 children and were attended by a variety of ages starting from 3 years old to junior high school level. The results of the implementation of this service activity provide an illustration that through the implementation of the among system, indicators of success in achieving children's literacy skills can emerge. Keywords: literacy, capacity, among system